Characterization of radiochromic film to measure small photon field output factors - Mabhengu, Thulani (My University, 2024)
AIM: This study aimed to investigate radiochromic (EBT3 type) film’s characteristics for the measurement of small photon field output factors and beam profiles for the field sizes ranging from 0.5 x 0.5 cm2 to 10 x 10 cm2 for the three photon energies, 6MV flattening filter free (FFF), 6MV flattening filter (FF), and 10MV FF. MATERIALS AND METHODS: Small-field dosimetry poses significant challenges and remains an active area of research in medical physics. In this study, radiochromic film (RCF), specifically Gafchromic EBT3 was used for small field measurements. The performance of RCF was compared with other conventional detectors such as ionization chambers, and a two-dimensional (2- D) detector amorphous silicon electronic portal imaging device (a-Si EPID). In addition, a comparison of the film measurements with software-calculated data, i.e, treatment planning system (TPS) was conducted. RESULTS: The field output factors (FOF) measured with EBT3 film compared to the TPS data for the smallest field size of 0.5 x 0.5 cm2 was found to be less or equal to 0.06% in all three photon energies. Volumetric detectors in 6MV FF beam showed an increase in % difference of up to 0.3 higher than the EBT3 film and TPS data. A higher quantitative percentage difference of 0.6% in FOF measured with a-Si EPID compared with the RCF data was observed in the smallest field size of 0.5 x 0.5 cm2 in higher energy beam, 10MV FF beam. CONCLUSION: The properties of RCF such as tissue-equivalent, less photon perturbation as well as volume averaging effects improve the accuracy of FOF measurements in small-fields compared to the ionization chambers utilized in this study. Therefore, RCF could serve as a reliable reference detector for small-field measurements.
A research report submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2023
Keywords: Radiochromic; Photon